Simon Sort of Says - Bow, Erin (Los Angeles : Disney Hyperion, 2023)
Two years after a tragedy saddles him with viral fame, twelve-year-old Simon O'Keeffe and his family move to Grin And Bear It, Nebraska, where the internet and cell phones are banned so astrophysicists can scan the sky for signs of alien life, and where, with the help of two new friends, a puppy, and a giant radio telescope, Simon plans to restart the narrative of his life.
Keywords: Psychic trauma -- Juvenile fiction; School shootings -- Juvenile fiction; Interstellar communication -- Juvenile fiction; Psychic trauma -- Fiction; School shootings -- Fiction; Interstellar communication -- Fiction; Juvenile fiction